2009
DOI: 10.2139/ssrn.1582665
|View full text |Cite
|
Sign up to set email alerts
|

Torture: Who Knew? An Analysis of the FBI and Department of Defense Reactions to Harsh Interrogation Methods at Guantanamo

Abstract: I witnessed SGT [REDACTED] placing lotion in her hand and touching a detainee. She was whispering in the detainee's ear as her hand traveled to the detainee's lap. I didn't see her hands (because her body obstructed my view) touch the detainee's groin, but the detainee started to grimace in pain. Later, a Marine told me that SGT [REDACTED] bent the detainee's thumbs back. He went on to say that "if you think that this is bad, she has done worse." 1 [The Government's investigation] found no evidence of torture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Army interrogator Lagouranis (Lagouranis & Mikaelian, 2007) reported that abuse reports he made to the Army Criminal Investigation Division during his service in Iraq (2004–2005) simply disappeared. The record of the last 15 years is replete with evidence of the nonperformance of internal accountability mechanisms, from the firing of General Taguba for failing to conceal command responsibility for abuse at Abu Ghraib (Hersh, 2007), to so-called “investigations” by the military ignoring key evidence (e.g., Denbeaux, Dembaux, & Gratz, 2010). And all attempts at civil sector accountability via licensing boards and APA ethics processes for possible psychologist involvement in detainee abuse did not result in a single opened investigation, much less sanctions.…”
Section: Key Considerations For Development Of Ethical Practice In Op...mentioning
confidence: 99%
“…Army interrogator Lagouranis (Lagouranis & Mikaelian, 2007) reported that abuse reports he made to the Army Criminal Investigation Division during his service in Iraq (2004–2005) simply disappeared. The record of the last 15 years is replete with evidence of the nonperformance of internal accountability mechanisms, from the firing of General Taguba for failing to conceal command responsibility for abuse at Abu Ghraib (Hersh, 2007), to so-called “investigations” by the military ignoring key evidence (e.g., Denbeaux, Dembaux, & Gratz, 2010). And all attempts at civil sector accountability via licensing boards and APA ethics processes for possible psychologist involvement in detainee abuse did not result in a single opened investigation, much less sanctions.…”
Section: Key Considerations For Development Of Ethical Practice In Op...mentioning
confidence: 99%